Does Gender Leave an Epigenetic Imprint on the Brain? - Cortes, Laura R.; Cisternas, Carla D.; Forger, Nancy G. (Frontiers in Neuroscience, 2019)
The words “sex” and “gender” are often used interchangeably in common usage. In fact, the Merriam-Webster dictionary offers “sex” as the definition of gender. The authors of this review are neuroscientists, and the words “sex” and “gender” mean very different things to us: sex is based on biological factors such as sex chromosomes and gonads, whereas gender has a social component and involves differential expectations or treatment by conspecifics, based on an individual’s perceived sex. While we are accustomed to thinking about “sex” and differences between males and females in epigenetic marks in the brain, we are much less used to thinking about the biological implications of gender. Nonetheless, careful consideration of the field of epigenetics leads us to conclude that gender must also leave an epigenetic imprint on the brain. Indeed, it would be strange if this were not the case, because all environmental influences of any import can epigenetically change the brain. In the following pages, we explain why there is now sufficient evidence to suggest that an epigenetic imprint for gender is a logical conclusion. We define our terms for sex, gender and epigenetics, and describe research demonstrating sex differences in epigenetic mechanisms in the brain. We then give several examples of how gender, rather than sex, may cause the brain epigenome to differ in males and females, and finally consider the myriad of ways that sex and gender interact to shape gene expression in the brain.